Synthesis of some quinazolinones inspired from the natural alkaloid L-norephedrine as EGFR inhibitors and radiosensitizers - Mostafa M. Ghorab; Maged S. Abdel-Kader; Ali S. Alqahtani; Aiten M. Soliman (Taylor & Francis Group, 2021)
A set of quinazolinones synthesized by the aid of L-norephedrine was assembled to generate novel analogues as potential anticancer and radiosensitizing agents. The new compounds were evaluated for their cytotoxic activity against MDA-MB-231, MCF-7, HepG-2, HCT-116 cancer cell lines and EGFR inhibitory activity. The most active compounds 5 and 6 were screened against MCF-10A normal cell line and displayed lower toxic effects. They proved their relative safety with high selectivity towards MDA-MB-231 breast cancer cell line. Measurement of the radiosensitizing activity for 5 and 6 revealed that they could sensitize the tumour cells after being exposed to a single dose of 8 Gy gamma radiation. Compound 5 was able to induce apoptosis and arrest the cell cycle at the G2-M phase. Molecular docking of 5 and 6 in the active site of EGFR was performed to gain insight into the binding interactions with the key amino acids.